The oxidation of 2-(2-methoxyethoxy)-ethanol and 2-(2-ethoxyethoxy)-ethanol by dihydroxydiperiodato nickelate(IV): A kinetic and mechanistic study - Shan, Jinhuan; Zhang, Ziwei (European Journal of Chemistry, 2014)
The kinetics of oxidation of 2-(2-methoxyethoxy)-ethanol and 2-(2-ethoxyethoxy)-ethanol by dihydroxydiperiodato nickelate(IV) (DPN) had been studied spectrophotometrically in alkaline medium in the temperature range of 293.2 to 313.2 K. The reaction rate showed first order dependence on DPN, 2-(2-methoxyethoxy)-ethanol and 2-(2-ethoxyethoxy)-ethanol. It was found that the pseudo-first-order rate constant kobs increased with an increase in concentration of OH- and a decrease in concentration of IO4-. There was a positive salt effect and no free radicals were detected. A plausible mechanism is proposed and the rate equations derived from the mechanism can explain all the experimental observations.